2022
DOI: 10.1186/s12871-022-01931-y
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anesthesia clinic childbirth course combined with labor epidural analgesia is associated with a decreased risk of postpartum depression : a prospective cohort study

Abstract: Background Postpartum depression (PPD) is a serious complication commonly seen in postnatal women. In this paper, an investigation was conducted to see if obstetric anesthesia clinic childbirth course combined with labor epidural analgesia (LEA) was associated with a decreased risk of PPD. Methods Six hundred fifty-five nulliparous women were enrolled in this prospective cohort study. The parturients were divided into 4 groups, with Group C being t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Tong et al found that participation in an obstetrical anesthesia clinic combined with epidural anesthesia was associated with a lower rate of PPD. 54 …”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tong et al found that participation in an obstetrical anesthesia clinic combined with epidural anesthesia was associated with a lower rate of PPD. 54 …”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Tong et al found that participation in an obstetrical anesthesia clinic combined with epidural anesthesia was associated with a lower rate of PPD. 54 A positive modification of the identifiable risk factors could predictably promote an emotionally more fulfilling birth experience and faster postpartum recovery both physically and psychologically. Traumatic birth experience and postpartum psychological derangements have short-and long-term negative impact on both the mother and the newborn (eg, suicide, killing the newborn, feeding difficulties, impaired psychosocial development of the newborn).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[6][7][8] As labor analgesia techniques and concepts have been vigorously implemented in China over the past few years, labor epidural analgesia has been extensively performed in various midwifery institutions nationwide. 9,10 It is worth noting that with the gradually increased rate of labor epidural analgesia, the incidence of PUR has become more widespread and complicated. Existing research has suggested that epidural anesthesia is a vital risk factor for overt PUR.…”
Section: Introductionmentioning
confidence: 99%